2008
DOI: 10.1007/s10661-008-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination in soil alongside mountain railway in Sichuan, China

Abstract: Heavy metal concentration in soil was investigated at three sites with different topography (cut slope, flat and embankment) within the vicinity of Chengdu-Kunming railway in Sichuan, China. Surface soil was sampled at certain distances from the track at each site and was analyzed for Cu, Mn, Pb, Zn, Cd by atomic absorption spectrometry. Cu, Cd and Zn concentrations in some soil exceeded the thresholds for non-polluted soil following the soil quality standard set by the State Environmental Protection Agency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 22 publications
(18 reference statements)
7
64
1
1
Order By: Relevance
“…The soil contents of Cu, Zn, Cd and Pb were among the five heavy metals significantly correlated with the distance from the highway (p b 0.01), indicating that the contents of these heavy metals in the topsoil along the Qinghai-Tibet highway were higher in samples taken nearer the road. Some studies have shown that the contents of traffic-related metals in topsoil decrease with increasing distance from the road edge (Liu et al, 2009;Yan et al, 2013;Werkenthin et al, 2014). These results support the suggestion that the contents of Cu, Zn, As, Cd and Pb in soils were closely related to traffic.…”
Section: Relationship Between Heavy-metal Contents In Roadside Soils supporting
confidence: 75%
See 1 more Smart Citation
“…The soil contents of Cu, Zn, Cd and Pb were among the five heavy metals significantly correlated with the distance from the highway (p b 0.01), indicating that the contents of these heavy metals in the topsoil along the Qinghai-Tibet highway were higher in samples taken nearer the road. Some studies have shown that the contents of traffic-related metals in topsoil decrease with increasing distance from the road edge (Liu et al, 2009;Yan et al, 2013;Werkenthin et al, 2014). These results support the suggestion that the contents of Cu, Zn, As, Cd and Pb in soils were closely related to traffic.…”
Section: Relationship Between Heavy-metal Contents In Roadside Soils supporting
confidence: 75%
“…Road transportation has increased alongside rapid economic development, resulting in a sprawling road network in China. Road transportation is one of the most significant sources of heavy metal pollution and plays an important part in the biogeochemical cycles of trace metals (Liu et al, 2009;Khan and Kathi, 2014). The combustion of liquid fuels, vehicular abrasion and the weathering of track or road materials can release particles containing heavy metals (Suzuki et al, 2009; Science of the Total Environment 521-522 (2015) [160][161][162][163][164][165][166][167][168][169][170][171][172] 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese investigators (Liu et al, 2009) studied heavy metal concentration in soil within the vicinity of mountain railway in Sichuan. Cu, Mn, Cd and Zn concentrations were elevated in top soil in the railway surroundings, whilst Pb showed no significantly raised level.…”
Section: Contaminationmentioning
confidence: 99%
“…The study of traffic-related metals in roadside soils along the Qinghai-Tibet highway indicated that Cu, Zn, Pb, Cr, Cd, and As were related to road transportation (Zhang et al 2015) and the contents of Zn, Pb, and Cd in roadside soils decreased exponentially with the distance from the road (Yan et al 2013;Zhang et al 2015). The heavy metal in soil alongside mountain railway in Sichuan showed that the concentrations of Cu, Zn, Mn, Pb, and Cd decreased with increasing distance from the railroad and indicated that railway transport was the source of such pollutants (Liu et al 2009 The third group of metals, Hg and As, indicated that the traffic did not affect both of elements because in this study area, the concentration of Hg and As did not decrease with increasing distance from the highway. It is generally believed that the coal combustion and solid waste incineration and wastewater discharge were generally regarded as the main pollution resource of Hg and As.…”
Section: Discussionmentioning
confidence: 99%